A gravimetric analysis of protein–oligosaccharide interactions. (1st April 2003) - Rudd, T.; Gallagher, J.T.; Ron, D.; Nichols, R.J.; Fernig, D.G.
Abstract : Interactions between an immobilized, heparin-derived octasaccharide and growth factors have been observed using a quartz crystal microbalance-dissipation (QCM-D). This device can measure the amount of growth factors binding to the octasaccharide surface and also the change of dissipation of the surface. Dissipation is a measure of how the adhered material 'damps' the surface vibrations. The octasaccharides were anchored through their reducing ends by the intermediary of the alkanethiol molecule, which covalently binds to the crystal surface through the thiol group. As expected, heparin sulphate binding growth factors bound to the octasaccharide, but the change in mass of growth factor bound per unit change in dissipation is different for the different growth factors. Suggesting that the structures of the various growth factor–octasaccharide complexes are different, therefore, indicates that the change in dissipation can give insights into the structure, orientation and packing of the oligosaccharide-growth factor complexes.